AKIBAT HUKUM PEMBATALAN AKTA PERJANJIAN PENGIKATAN JUAL BELIi (PPJB) YANG DiKERJAKAN OLEH DEBITUR TANPA MEMENUHI PRESTASI DALAM PERJANJIAN (STUDI PUTUSAN NOMOR: 571/PDT/2017/PT.BDG) - Sesa Merindah Putri; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2019)
The agreement is an event in which a person pledges to another person to know where two people promise to do one thing. to be able to make an agreement then it must fulfill the legal requirements of an agreement set forth in article 1320 of the law of civil law. upon fulfillment of the parties may enter into a sale and purchase agreement where prior to the sale and purchase of the parties entered into a preliminary agreement which is commonly referred to as the sale and purchase agreement. in the execution of the sale and purchase agreement of the parties sometimes does not conform to what is entered into in the agreement, so the agreement can be canceled by the party. the factor is affecting cancellation of deed and sale and purchase agreement are the sale price agreed upon in the agreement not being repaid by the buyer until the agreed period of time.